2022
DOI: 10.1016/j.jpsychires.2021.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Does perceived post-traumatic growth predict better psychological adjustment during the COVID-19 pandemic? Results from a national longitudinal survey in the USA

Abstract: Perceiving that one has grown in positive ways following highly stressful experiences (perceived posttraumatic growth; PPTG) is common and sometimes--but not always--related to psychological wellbeing. However, PPTG is typically studied cross-sectionally and well after the stressful experience has passed; how PPTG might relate to wellbeing over time in an unprecedented, ongoing worldwide disaster such as the COVID-19 pandemic remains unknown. Thus, the current study sought to answer whether, in the midst of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 55 publications
0
18
0
1
Order By: Relevance
“…Literature points out the significant association between post-traumatic stress and post-traumatic growth. Growth is associated with the presence rather than the absence of post-traumatic stress symptoms (Dekel, Ein-Dor, & Solomon, 2012 ; Park, Wilt, Russell, & Fendrich, 2022 ). Indeed, the distress may progressively trigger accommodation of the event into the patient’s perspective and result in post-traumatic growth (Tedeschi & Calhoun, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature points out the significant association between post-traumatic stress and post-traumatic growth. Growth is associated with the presence rather than the absence of post-traumatic stress symptoms (Dekel, Ein-Dor, & Solomon, 2012 ; Park, Wilt, Russell, & Fendrich, 2022 ). Indeed, the distress may progressively trigger accommodation of the event into the patient’s perspective and result in post-traumatic growth (Tedeschi & Calhoun, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the distress may progressively trigger accommodation of the event into the patient’s perspective and result in post-traumatic growth (Tedeschi & Calhoun, 2004 ). Park et al ( 2022 ) pointed out that awareness and perceptions of growth can aid individuals in the adaptation process, thus acting as an effective coping mechanism. Future studies could further investigate the role of post-traumatic growth and explore whether longer psychological support could prevent psychological sequelae in COVID-19 inpatients, even in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the obtained research results, it can be hypothesized that too high an intensity of traumatic stress causes a negative perception of the consequences of a pandemic. Chen et al [ 50 ] obtained similar results amongst nurses, while Park et al [ 51 ] confirmed this relationship among Amazon MTurk employees. Thus, PTG is associated with the symptoms of post-traumatic stress disorder and can be treated as a coping mechanism in the face of persistent suffering from trauma [ 52 ].…”
Section: Discussionmentioning
confidence: 79%
“…Studies on the personal strength factors suggest that veterans with strong coping self-efficacy and hope suffer less from PTSD. 19,20,21 War against terror was not a traditional war. The active-duty officials of police who had participated in this war and had direct and repeated exposure of trauma showed high levels of PTG and scored high in personal strength factors like hope and coping selfefficacy, results are persistent with previous research.…”
Section: Discussionmentioning
confidence: 99%